Vascular plants of Pilzno surroundings (South-Eastern Poland) - Towpasz, Krystyna (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2019)
The paper presents the occurrence of vascular plant species in the southern part of the Pilzno commune based on monographic studies from the area of Ciężkowice and Strzyżów Foothills (Western Carpathians). The study contains a list of plant species, both native and of alien origin. For each species its habitat and sites in the ATPOL network were given.